APVO210: A Bispecific Anti-CD86-IL-10 Fusion Protein (ADAPTIR™) to Induce Antigen-Specific T Regulatory Type 1 Cells - Pellerin, Laurence; Chen, Ping; Gregori, Silvia; Hernandez-Hoyos, Gabriela; Bacchetta, Rosa; Roncarolo, Maria Grazia (Frontiers in Immunology, 2018)
IL-10 is a potent immunosuppressive cytokine that promotes the differentiation of tolerogenic dendritic cells (DC-10), and the subsequent induction of antigen-specific T regulatory type 1 (Tr1) cells, which suppress immune responses. However, IL-10 acts on multiple cell types and its effects are not solely inhibitory, therefore limiting its use as immunomodulant. APVO210 is a bispecific fusion protein composed of an anti-CD86 antibody fused with monomeric IL-10 (ADAPTIRTM from Aptevo Therapeutics). APVO210 specifically induces IL-10R signaling in CD86+ antigen-presenting cells, but not in T and B cells. In this study, we tested whether APVO210 promotes the differentiation of tolerogenic DC-10 and the differentiation of antigen-specific CD4+ Tr1 cells in vitro. We compared the effect of APVO210 to that of recombinant human IL-10 on the in vitro differentiation of DC-10, induction of alloantigen-specific anergic CD4+ T cells (T-allo10), enrichment in CD49b+ LAG3+ Tr1 cells mediating antigen-specific suppression, and stability upon exposure to inflammatory cytokines. APVO210 induced the differentiation of tolerogenic DC (DC-A210) that produced high levels of IL-10, expressed CD86, HLA-G, and intermediate levels of CD14 and CD16. These DC-A210 induced alloantigen-specific anergic T-cell lines (T-alloA210) that were enriched in CD49b+ LAG3+ Tr1 cells, produced high levels of IL-10, and had suppressive properties. The phenotype and high IL-10 production by DC-A210, and the alloantigen-specific anergy of T-alloA210 were preserved upon exposure to the inflammatory cytokines IL-L-6and TNF-α. The effects of APVO210 were comparable to that of dimeric recombinant human IL-10. In conclusion, our data demonstrate that APVO210 drives the differentiation of tolerogenic DC and functional alloantigen-specific Tr1 cells in vitro. Since APVO210 specifically targets CD86+ cells, we hypothesize that it will specifically target CD86+ DC to induce Tr1 cells in vivo, and mediate antigen-specific immunological tolerance by induction of tolerogenic DC and Tr1 cells.